European dimension in the referenda campaigns - Jurgelionytė, Aušrinė (Information & Media, 2015)
The referenda of the 21st century were also inevitably related with the European dimension: the referendum in 2003 on the membership of the Republic of Lithuania in the European Union (EU); the referendum of 2008 on exceeding the operation of the Ignalina Nuclear Power Plant (INPP); the referendum of 2013 on building a new nuclear power plant in the Republic of Lithuania; and the referendum of 2014 on land for sale to foreigners. These four referenda are the object of this paper. It analyses the reflections of the European dimension in the referenda campaigns. The campaign slogans are mainly taken into account when reconstructing various discursive devices. The explanatory power of the new institutionalism (discursive) theories is discussed.